Juridical review of the comparison of remuneration policies in omnibus law with labor law number 13 of 2003 - Roswita Sitompul; Kartina Pakpahan; Ferina Diamond (Magister Kenotariatan Universitas Pasundan, 2021)
Demand is growing rapidly, but the economy is still weak, employment is limited, unemployment continues to increase. Effective regulation is needed in the recovery of various sectors of the economy. The government formed the Omnibus Law to face the challenges of the times, reduce unemployment and attract new entrepreneurs. The research method is empirical law. The research characteristic is descriptive analysis with qualitative research. The research shows that the omnibus law was formed because the government felt there was a lack of implementation of policies by Law Number 13 of 2003, especially the provision of severance pay so that there were still widespread differences in interests between workers and employers. As a result, many people do not dare to start a business. The difference in remuneration arrangements in Omnibus Law is arrangements for workers' severance pay and compensation for contract workers. The time limit for contract workers is a maximum of 3 (three) years of work being changed to 5 (five) years and extended to a maximum of 5 (five) years. The advantages of Omnibus Law are mobilization of the investment climate and employment opportunities, providing compensation for workers, increasing overtime wages. Lack of public participation in the formation of laws, and weak legal transparency make rejection of workers who feel disadvantaged by the lack of severance pay, the elimination of district/city minimum wages, and wages during leave. Hope that government will form regulations openly and pay attention to workers' rights without prejudice to common interests.